SEC61 translocon gamma subunit is correlated with glycolytic activity, epithelial mesenchymal transition and the immune suppressive phenotype of lung adenocarcinoma - Zhou Changshuai; Cui Huanhuan; Yang Yuechao; Chen Lei; Feng Mingtao; Gao Yang; Li Deheng; Li Liangdong; Chen Xin; Li Xiaoqiu; Cao Yiqun (Acta Biochimica et Biophysica Sinica)
Lung adenocarcinoma (LUAD) remains a predominant cause of cancer-related mortality globally, underscoring the urgency for targeted therapeutic strategies. The specific role and impact of the SEC61 translocon gamma subunit (SEC61G) in LUAD progression and metastasis remain largely unexplored. In this study, we use a multifaceted approach, combining bioinformatics analysis with experimental validation, to elucidate the pivotal role of SEC61G and its associated molecular mechanisms in LUAD. Our integrated analyses reveal a significant positive correlation between SEC61G expression and the glycolytic activity of LUAD, as evidenced by increased fluorodeoxyglucose (FDG) uptake on positron emission tomography (PET)/CT scans. Further investigations show the potential influence of SEC61G on metabolic reprogramming, which contributes to the immunosuppressive tumor microenvironment (TME). Remarkably, we identify a negative association between SEC61G expression levels and the infiltration of critical immune cell populations within the TME, along with correlations with immune checkpoint gene expression and tumor heterogeneity scores in LUAD. Functional studies demonstrate that SEC61G knockdown markedly inhibits the migration of A549 and H2030 LUAD cells. This inhibitory effect is accompanied by a significant downregulation of key regulators of tumor progression, including hypoxia-inducible factor-1 alpha (HIF-1α), lactate dehydrogenase A, and genes involved in the epithelial-mesenchymal transition pathway. In conclusion, our comprehensive analyses position SEC61G as a potential prognostic biomarker intricately linked to glycolytic metabolism, the EMT pathway, and the establishment of an immune-suppressive phenotype in LUAD. These findings underscore the potential of SEC61G as a therapeutic target and predictive marker for immunotherapeutic responses in LUAD patients.